2015
DOI: 10.3389/fneur.2015.00100
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Associated with Early and Late Chronotypes in Drosophila melanogaster

Abstract: The circadian clock provides the temporal framework for rhythmic behavioral and metabolic functions. In the modern era of industrialization, work, and social pressures, clock function is jeopardized, and can result in adverse and chronic effects on health. Understanding circadian clock function, particularly individual variation in diurnal phase preference (chronotype), and the molecular mechanisms underlying such chronotypes may lead to interventions that could abrogate clock dysfunction and improve human (an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 28 publications
2
16
1
Order By: Relevance
“…Notably, a comparison of gene expression between diurnal and nocturnal flies highlighted just a single core clock gene (pdp1). This finding is reminiscent of the results of our previous study in flies [37], where transcriptional differences between early and late chronotypes were present in genes up-and downstream of the clock but not in the clock itself. The phase conservation of core clock genes in diurnal and nocturnal animals has also been documented in mammals [38][39][40].…”
Section: Discussionsupporting
confidence: 83%
“…Notably, a comparison of gene expression between diurnal and nocturnal flies highlighted just a single core clock gene (pdp1). This finding is reminiscent of the results of our previous study in flies [37], where transcriptional differences between early and late chronotypes were present in genes up-and downstream of the clock but not in the clock itself. The phase conservation of core clock genes in diurnal and nocturnal animals has also been documented in mammals [38][39][40].…”
Section: Discussionsupporting
confidence: 83%
“…Secondly, there may also be a genetic vulnerability in late sleepers that may predispose them to metabolic dysregulation . An animal study demonstrated that chronotype diversity was largely mediated by genes and molecular processes were entirely different in evening and morning chronotype . Recently, a genome‐wide association study of self‐reported chronotype within the UK Biobank cohort (n = 100 420) found that several novel genetic loci were significantly associated with chronotype …”
Section: Discussionmentioning
confidence: 99%
“…Thus, the observed latitudinal cline in TIM polymorphism appears to be an evolutionary adaptation to the conditions at higher latitudes (Kyriacou, Peixoto, Sandrelli, Costa, & Tauber, ). Polymorphisms appear also present in CRY, but a clear latitudinal cline was so far not observed (Pegoraro et al., ).…”
Section: The Molecular Basis Of the Circadian Clock In D Melanogastementioning
confidence: 98%